Characterization of wound-responsive RNA-binding proteins and their splice variants in Arabidopsis - Bove, Jérôme; Kim, Cha Young; Gibson, Caroline A; Assmann, Sarah M (Plant molecular biology, 2008)
We report the characterization of three UBA2 genes (UBA2a, -b, and -c; corresponding to At3g56860, At2g41060, and At3g15010) encoding Arabidopsis thaliana proteins with high homology to Vicia faba AKIP1 and other heterogeneous nuclear ribonucleoprotein (hnRNP)-type RNA-binding proteins. In vitro RNA binding assays revealed that the three UBA2 proteins interact efficiently with homoribopolymers. Biolistic transient expression of UBA2-GFPs demonstrated that the three UBA2 proteins localize to the nucleus. Expression analysis by RNA gel blot, RT-PCR, and promoter::GUS assays showed that UBA2 transcripts are present in all organs. UBA2 genes are subject to alternative splicing affecting only the 3'-untranslated regions (UTRs): six different splice variants were detected for UBA2a, and two each were found for UBA2b and UBA2c. RT-PCR and quantitative real-time RT-PCR analysis showed that the levels of UBA2 transcripts are regulated by wounding in a splice variant-specific manner: splice variants UBA2a.1 and UBA2c.1 increased following mechanical wounding. Wounding effects on gene expression are transduced by methyl jasmonate (MeJA)-dependent and oligogalacturonide (OGA)-dependent pathways. However, neither MeJA nor OGA treatment altered levels of any of the UBA2 transcripts, and other plant hormones implicated in wound responses, ethylene and abscisic acid (ABA), also had no effect on accumulation of UBA2 transcripts. Taken together, these results imply that the three UBA2 genes encode hnRNP-type nuclear RNA-binding proteins that function in a novel wound signal transduction pathway.